Exploring Social Capital in Chile's Coastal Benthic Comanagement System Using a Network Approach - Andrés Marín; Stefan Gelcich; Juan C. Castilla; Fikret Berkes (Ecology and Society, 2012)
Comanagement success relies on the proper administration of resources and on the capacity of users to establish and maintain positive social relationships with multiple actors. We assessed multifunctional relationships of small-scale artisanal fisher organizations engaged in a coastal benthic resources comanagement system in Chile to explore bridging and linking social capital, using an egocentric network approach. The formal leaders of 38 small-scale fisher organizations were surveyed to investigate (1) similarities and differences in social capital among fisher organizations and regions, and (2) possible effects of social capital levels on comanagement performance. Results show that the best performing fisher organizations are those with higher levels of linking and bridging social capital. Positive and strong correlations exist between linking social capital levels and comanagement performance variables. Importantly, fisher organizations considered to manage resources successfully consistently presented high levels of linking social capital, irrespective of variability in bridging social capital. Using egocentric networks allows understanding actors' differences in the comanagement social structure, thus providing critical insights for improving comanagement systems.